Faktor-Faktor yang Mempengaruhi Perilaku Etis Mahasiwa Akuntansi: (Studi Pada Mahasiswa Akuntansi Perguruan Tinggi Swasta Di Surakarta) - Fediana Asriani Sekartaji; Suhendro Suhendro; Rosa Nikmatul Fajri (Owner : Riset dan Jurnal Akuntansi, 2020)
This study aims to analyze the factors that influence ethical behavior of accounting students, including Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence, Understanding of Accounting Ethics, Gender and Eti Behavior. The population in this study is accounting students in all private universities in Surakarta. The sampling technique uses purposive sampling, with the criteria of students who have taken auditing courses I and II, so we get a sample of 100 respondents. Quantitative research type. Data sources in the form of Primary. Analysis of the data used is multiple linear regression analysis. The results showed that intellectual intelligence had no effect on the ethical behavior of..accounting students, while emotional intelligence, spiritual intelligence, understanding of the accounting ethics code, gender..influenced the ethical behavior of accounting students.